Weed management through oxyfluorfen in direct seeded rice and its impact on soil micro-organisms and succeeding crops - Poddar, R.; Ghosh, R.K; Paul, T.; Bera, S. (Annals of Agricultural Research, 2016)
A field experiment was conducted during rainy seasons of 2009 and 2010 at Kalyani C-Block Farm of BCKV, Mohanpur, West Bengal, to evaluate the bio-efficacy of oxyfluorfen and its impact on soil micro-organisms and succeeding crop in direct seeded rice. The experiment was carried out with 7 treatments viz. T1, Control (no weeding); T2, Check-oxyfluorfen @ 200 g/ha; T3, Oxyfluorfen @ 150 g/ha; T4, Oxyfluorfen @ 200 g/ha; T5, Oxyfluorfen @ 250 g/ha; T6, Oxyfluorfen @ 300 g/ha; T7, Oxyfluorfen @ 400 g/ha. The results showed that the treatment T7 controlled the weeds most effectively which produced the highest seed yield. The micro-flora population was affected after application of herbicides, but later it reached to a higher level. There was no influenced on the succeeding crop in terms of plant population, but T4 treatment resulted in higher yield of all the succeeding crops.